HUBUNGAN TINGKAT PENGETAHUAN PATIENT SAFETY TERHADAP KEPATUHAN PERAWAT DALAM PENERAPAN SURGICAL SAFETY CHECKLIST DI RUANG PRE OPERASI INSTALASI KAMAR OPERASI RSD MANGUSADA BADUNG - Agnihortry, Putu Ayu Mega; Susila, I Made Dwie Pradnya; Kusuma, A.A. Ngurah Nara (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Patient safety has now become a global issue and a critical component of hospital quality management. One of the components in patient safety that must be carried out in the operating room is the application of the surgical safety checklist. Adherence in implementing the surgical safety checklist is influenced by several factors such as the knowledge of patient safety that nurses have. This study aims to determine the relationship between the level of patient safety knowledge and the compliance of nurses in implementing the surgical safety checklist in the Pre-Operation Room, the Operation Room, RSD Mangusada Badung. This study used a quantitative observational method with a cross sectional design. The sample was all nurses in the operating room installation room RSD Mangusada Badung who were selected by a total sampling of 41 people. The research was conducted from 01-31 October 2020. The results of data analysis using the rho Spearman nonparametric statistical test at a significance level of ? 0.05, the p value was 0.000 <0.05. This shows that there is a significant relationship between the level of patient safety knowledge on nurses' compliance in implementing the surgical safety checklist in the Pre-Operation Room for the Operation Room, RSD Mangusada Badung. It is hoped that health workers, especially nurses in the operating room, can increase knowledge about patient safety and be more obedient in implementing the surgical safety checklist.